Implementation of The ATIK Model to Improve Gross Motoric Ability Bakiak Games in TKIT Nurussunnah Batam - Yayuk Winarsih; Yanti Komala; Epah Maspupah; Sri Watini (CV. Pusdikra Mitra Jaya, 2023)
Play activities are fun activities in the PAUD unit, because they are part of motor development for children that must be properly stimulated. One way to stimulate children's motor skills is through various kinds of games, one of which is the traditional bakiak game. This study aims to describe the increase in children's gross motor skills, especially coordination of eye and leg movements, body with balance, and agility and leg strength in group B children at TKIT Nurussunnah Batam through playing clogs. The benefits of this study are to improve children's gross motor skills through playing clogs according to the abilities of children, so that the ability to balance, and agility and leg strength can be properly stimulated. Teachers are required to develop creative and holistic learning models, especially in the learning process of children who have different characters and needs. One model of early childhood learning that is very well known is the ATIK model (Observe, Imitate and do). Early childhood in their learning growth starts from observations obtained from stimulation of the surrounding environment by using body sensing to observe and then imitate as a result of learning that is obtained to be further worked on by practicing playing bakiak with a team/group. This research was made using descriptive qualitative. The use of the ATIK model in playing bakiak activities at TKIT Nurussunnah Batam can improve children's abilities to develop gross motor skills.